Effect of long-term un-treated domestic wastewater re-use on soil quality, wheat grain and straw yields and attributes of fodder quality - Simmons, Robert W.; Ahmad, W.; Noble, A.D.; Blümmel, Michael; Evans, A.; Weckenbrock, P. (Springer, 2010)
In 2006 a comprehensive sampling program was undertaken in two pre-selected peri-urban villages in Faisalabad, Pakistan to evaluate the soil and agronomic impacts of long-term (25–30 years) untreated wastewater re-use on wheat grain and straw yields and attributes of wheat straw fodder quality. Soil SAR, ESP, RSC and ECe were 63%, 37%, 31%, and 50% higher under wastewater (WW) as compared with canal water (CW) irrigated plots. Further, 2.7 and 6.65 fold increases in soil NO3− + NO2− - N and Olsen-P were observed in WW as compared with CW irrigated plots. However, no significant differences in grain yield, wheat straw biomass, or fodder quality attributes were observed between WW and CW irrigated plots. In addition, for both CW and WW irrigated plots wheat straw, Cd and Pb concentrations were orders of magnitude below the EC Maximum permissible levels for Pb and Cd in feed materials and thus pose no threat to the fodder-livestock food chain. Further, elevated soil N associated with WW irrigated plots has a significant (p < 0.01) positive influence on fodder quality by increasing the N content. Factorial ANOVA with covariance indicates that effective management of the elevated soil ECe in WW irrigated plots would increase grain yield and wheat straw biomass by 853 kg ha−1 (19.5%) and 819 kg ha−1 (18.6%) respectively as compared with CW irrigated plots. In Faisalabad, if managed appropriately to address emerging salinity issues the contribution of wastewater irrigation to the achievement of MDGs 1 and 7 could be significant if adverse impacts remain as marginal as found in this study.